Study on multi-size seed-metering device for vertical plate soybean precision planter - Hongxin, Liu; Lifeng, Guo; Lulu, Fu; Shifa, Tang (International Journal of Agricultural and Biological Engineering, 2015)
Aiming to solve the problem of small range of the appropriately sowing seeds existing in a vertical disc seed-metering device, the planter plate series with four sizes were developed according to the variety and size distribution of all soybeans in China. The structure and working principle of the vertical disc soybean seed-metering device were detailed, and the influence of the diameter of soybean on the working performance of the seed-metering device was analyzed through the software EDEM virtual simulation, so as to achieve the goal of covering the soybean seeds with all sizes by the minimum planter plate series as well as to obtain the most appropriate operating speed of each planter plate by optimization. For the planter plates with the hole diameter of 7, 9, 12, 16 mm, the appropriate size ranges of sowing seeds are 4.5-6.0, 6.0-8.0, 8.0-10.5, 10.5-13.0 mm, respectively, and the appropriate operating speeds are 9, 8, 7, 6 km/h, respectively. The results show that this planter plate series can meet the requirements of seeding with all sizes of soybeans at the range of the most appropriate operating speed. The study method can provide a reference for design and optimization of precision planters. DOI: 10.3965/j.ijabe.20150801.001 Citation: Liu H X, Guo L F, Fu L L, Tang S F. Study on multi-size seed-metering device for vertical plate soybean precision planter. Int J Agric & Biol Eng, 2015; 8(1): 1-8.